Pusat Penelitian Kelapa Sawit Berbasis Arsitektur Berkelanjutan di Kabupaten Mamuju Tengah - Alfina Lusiana; Ansarullah Ansarullah; Muhammad Zaki (Universitas Medan Area, 2026)
Central Mamuju Regency has significant potential as one of the leading palm oil production centers in West Sulawesi. However, there is currently no integrated research facility capable of supporting improvements in production quality, processing efficiency, and technological innovation. This study aims to design a Palm Oil Research Center concept that integrates research, education, and publication functions based on sustainable architectural principles. The methods used include literature review, field surveys, and site analysis to determine design strategies suitable for a humid tropical climate. The results show that applying proper building orientation, maximizing natural lighting, cross ventilation, the use of local materials, and the integration of renewable energy can optimize energy efficiency by up to 30% compared to conventional designs. The research center design is divided into three main zones: research, education, and public areas. This concept is expected to serve as a model for developing environmentally friendly agricultural research